2008
DOI: 10.5174/tutfd.2008.01180.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Related Factors On One And Two-year Mortality After A Hip Fracture In Elderly Turkish Patients

Abstract: Objectives: Hip fractures are one of the most serious causes of impairment and death in the elderly. The aim of this study is to identify the effects of different risk factors on mortality after a hip fracture in elderly Turkish patients.Patients and Methods: Two-hundred forty patients (>60 years; mean age 76.0±8.2 years) who were operated for fracture of the hip from 2001 to 2006 were investigated. Demographic data, preoperative length of hospital stay, anesthesia type and ASA physical status, albumin level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Since aging is associated with a decrease in the functional reserves of organ systems and an increase in the presence of comorbid conditions, advanced age has traditionally been considered a risk for surgery and anesthesia (7,8) . Though age is considered in many risk indices, age is not a contraindication for surgery and there are publications showing it does not affect mortality rates after hip fracture surgery (4)(5)(6)8,9) . In our study, we found the mean age of dead patients high, and it is thought that age is a significant factor regarding postoperative mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since aging is associated with a decrease in the functional reserves of organ systems and an increase in the presence of comorbid conditions, advanced age has traditionally been considered a risk for surgery and anesthesia (7,8) . Though age is considered in many risk indices, age is not a contraindication for surgery and there are publications showing it does not affect mortality rates after hip fracture surgery (4)(5)(6)8,9) . In our study, we found the mean age of dead patients high, and it is thought that age is a significant factor regarding postoperative mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…ASA classification is commonly used to determine preoperative comorbidities and risk factors (14) . The efficacy of ASA classification to determine postoperative mortality in elderly patients operated for hip fractures is controversial (3,5,6,9,10,15,16) . In our study of a heterogeneous patient group, 5 out of 88 patients in ASA 3 group, 7 out of 18 patients in ASA 4 group and 1 patient in ASA 5 group had died.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atay ve arkada?lannin çali^masinda, albumin düzeyinin dü §ük olmasinin bir ve iki yillik mortalité üzerine belirgin etkisi olmadigi belirtilmektedir (13). Çaliçma grubumuzdaki hastalann ameliyat öncesi albumin düzeyleri incelendiginde, 88 hastada hipoalbüminemi bulunmasi, bu hastalann oldukça dü^kün oldugunu, beslenmelerinin kötü oldugunu göstermektedir.…”
Section: Tartiçmaunclassified
“…Ek morbiditeler nedeniyle ya?li hastalarda yüksek American Society of Anesthesiologists (ASA) skorlari ile sik karçilaçilir. Ameliyat öncesi haziriik sürecinin ASA skoru yüksek oían hastalarda uzun olmasi nedeniyle ameliyat öncesi sûre uzayabilmektedir (13). Kink sonrasi erken dönemde ameliyat edilebilen hastalarda cerrahi sonuçlar geç dönemde ameliyat edilenlere göre daha iyidir (8).…”
Section: Tartiçmaunclassified